Clinicopathological and molecular characteristics of pediatric meningiomas. Issue 1 (13th September 2017) - Battu, Sudha; Kumar, Anupam; Pathak, Pankaj; Purkait, Suvendu; Dhawan, Linchi; Sharma, Mehar C.; Suri, Ashish; Singh, Manmohan; Sarkar, Chitra; Suri, Vaishali
Abstract : Molecular and clinical characteristics of pediatric meningiomas are poorly defined. Therefore, we analyzed clinical, morphological and molecular profiles of pediatric meningiomas. Forty pediatric meningiomas from January 2002 to June 2015 were studied. 1p36, 14q32 and 22q‐deletion were assessed by fluorescent in situ hybridization and mutations of most relevant exons of AKT, SMO, KLF4, TRAF and pTERT using sequencing. Expression of GAB1, stathmin, progesterone receptor (PR), p53 along with MIB‐1 LI was examined using immunohistochemistry. There were 36 sporadic and four NF2 associated meningiomas. Among sporadic meningiomas, the majority (72.2%) of cases harbored 22q‐deletion. Difference in frequency of combined 1p/14q deletion in Grade‐I versus Grade‐II/III tumors was not significant (13.7% vs 28.5%, P  = 0.57). PR immunoreactivity was seen in 65.5% of Grade‐I and 14.2% of Grade‐II/III tumors ( P  = 0.03). The majority (97.2%) of meningiomas were immunonegative for p53. Stathmin and GAB co‐expression was observed in 58.3% of cases. Notably, AKT, SMO, KLF4, TRAF7 (exon 17) and pTERT mutations were seen in none of the cases analyzed. 1p/14q codeletion was frequent in skull base as compared to non‐skull base meningiomas (23% vs 11.1%, P  = 0.37). All NF2 meningiomas harbored 22q‐deletion and showed GAB and stathmin co‐expression while none showed 1p/14q loss. Pediatric meningiomas share certain phenotypic and cytogenetic characteristics with adult counterparts, but GAB and stathmin co‐expression in the majority of cases and non‐significant difference in frequency of 1p/14q co‐deletion between low‐ and high‐grade meningiomas indicate an inherently aggressive nature. Characteristic AKT/SMO, KLF4/TRAF7 and pTERT genetic alterations seen in adults are distinctly absent in pediatric meningiomas.